AGOA a step forward for development? insights into the textile sectors of Lesotho and Namibia - Vlok, Sada (My University, 2010)
ABSTRACT This paper analyses the African Growth and Opportunity Act (AGOA) and the development aspects of the agreement. The aims and challenges of the agreement are explored specifically in the textile industry of both Lesotho and Namibia. This agreement has been scrutinized within the global economy today. Therefore the research project has outlined the theoretical and economic context in which AGOA is situated. The paper aims to show whether or not AGOA is a step forward in the development of both these countries and implies whether or not the agreement helps develop Less Developed Countries (LDCs) on the whole. The overall conclusion of AGOA and its link to economic growth (specifically to the textile industry) is that while the agreement is sound theoretically, it lacks the proper legislation and implementation to fully develop African countries. This leaves these countries stuck in the poverty trap and developed countries benefitting. While outlining the problems of AGOA, suggestions have been made for solutions that may lead to sustainable growth of LDCs and the AGOA agreement. These include a change in legislature, opening of dialogue, strong institutions to control the implementation and a monitoring and review system.